School-Family-Community Partnerships and Its’ Influence on Students ‘Achievement in Public Secondary Schools in Ilemela Municipal, Tanzania - Paulo, Veneranda; Oduor Onyango, Dr. Daniel (International Journal of Humanities and Education Development (IJHED), 2020)
Education is an investment which brings socio-economic return to the person and nation at large. In implementing various strategies to improve student development and academic outcomes, it is important to include all key stake holders by fostering close schools, family and community partnerships, and not only teachers and administrators, but also family and community members. These partnerships improve schools and lead to student’s success in academic and social arena. In Tanzania public secondary schools, family and community partnerships is considered to be low and students’ performance in academic and discipline continues to be poor compared to schools with strong family community partnerships. Therefore, the objectives of this study were; to identify the existing school-family-community partnerships in public secondary school in Ilemela Municipal, to investigate whether school-family-community partnerships in public secondary schools influence students ‘achievement in Ilemela Municipal and to find out if there are any challenges facing of school-family-community partnerships implementation in public secondary schools in Ilemela Municipal. The study employed a mixed research methods where questionnaires and interview were used to collect data. The total sample size was 141; respondents involved were teachers, heads of school, students, District Education Officer, and family and community members. Descriptive statistics analysis and thematic analysis was used, and the findings revealed that there are few and poor School-family community partnerships. The study found out that, partnerships have great influence on students ‘achievement. Furthermore, the study found various challenges which face the implementation of school-family-community partnerships in public secondary schools in Ilemela district. The study recommends that The Ministry of education and vocational training the Ministry of education to make policy reforms to encourage a national wide involvement of families and community in school development activities to ensure quality provision of education which will enhance best returns in socio-economic such as industrialized economy.